Pengukuran Dan Pemodelan Serat Optik Dalam Kondisi Terpapar Sinar Matahari - yadnya, Made Sutha; Zainuddin, Abdullah; Parhadi, Wahyu Chandra (LPPM Universitas Mataram, 2024)
Optical fiber is a transmission line or a type of cable made of glass fiber or plastic which is very fine and smaller than a strand of hair, and can be used to transmit light signals from one place to the recipient. Optical cables that float and hang openly exposed to sunlight, or are embedded exposed to burning rubbish cause additional attenuation which results in signal transmission which causes communication links to break. In this research, measurements and modeling were carried out of conditions assuming an increase in heat that occurred. These conditions are carried out on a laboratory scale. Optical isolation really protects the optical fiber. This modeling will predict the useful life of optical fiber which should be used in 30 years. The measurement results are tabulated and sorted so that the distribution of temperature increases is known.